Situación del mapeo microbiológico de uro cultivos en un hospital referencial de Perú 2013-2015: Situation of the microbiological mapping of urine cultures in a referral hospital of Peru 2013-2015 - Grandez-Urbina, J.Antonio (2022)
Abstract   Microbiological mapping is a tool and base for good antibiotic management. It guides the empirical treatments in the hospital services as well as in the updating of care protocols. Objective: To determine the situation of the microbiological mapping of urine cultures in referential hospital. Methods: A cross-sectional descriptive study of urine cultures of the different hospital services from the first semester of 2013 to 2015 was carried out. The situation was defined as the determination of the microbiological profile and the most frequent pathogens isolated. The percentage of resistance by extended-spectrum beta-lactamase (ESBL) for 3 consecutive years was determined. The data were collected and added to a database coded in double back up. Results: The most frequently isolated pathogens were E. coli (56.60%), K. pneumoniae (10.12%) and P. mirabilis (4.22%). The frequency of E. coli ESBL (+) in the years 2013, 2014, 2015 was 37.49%; 47.02% and 50.10% respectively. The sensitivity of E. coli was for ertapenem, meropenem and imipenem (99% -100%), tigecillin (99%) and the percentage of resistance of E. coli to Ciprofloxacin: 67%, 72% and 82% respectively. Conclusion: The most frequently isolated agent was E. coli. The frequency of E. coli ESBL (+) has increased by 33% (2013) to 50% by 2015, with an increase in resistance to ciprofloxacin. However, there is a therapeutic alternative (cefotaxime / clavulanic acid) whose sensitivity is greater than 90%. Key words: Microbiological analysis; Escherichia coli; Antibiotic therapy. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1268